2011
DOI: 10.1186/1751-0147-53-4
|View full text |Cite
|
Sign up to set email alerts
|

Udder pathogens and their resistance to antimicrobial agents in dairy cows in Estonia

Abstract: BackgroundThe goal of this study was to estimate the distribution of udder pathogens and their antibiotic resistance in Estonia during the years 2007-2009.MethodsThe bacteriological findings reported in this study originate from quarter milk samples collected from cows on Estonian dairy farms that had clinical or subclinical mastitis. The samples were submitted by local veterinarians to the Estonian Veterinary and Food Laboratory during 2007-2009. Milk samples were examined by conventional bacteriology. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
63
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 23 publications
20
63
1
4
Order By: Relevance
“…Antimicrobial sensitivity tests of Staphylococcus aureus as seen in this study agrees with earlier reports by Kalmus et al (2011), who reported a heightened resistance of Staphylococcus aureus to Penicillin and Ampicillin. There is no scientific evidence as to the resistance pattern of mastitis pathogens to penicillin and the Cephalosporin group, but there were widespread reports of antimicrobial drug resistance among Staphylococcus pathogens for over 2-3 decades as earlier reported by Kalmus et al (2011) in Estonia, Botrel et al (2010) in Germany; Persson et al, 2011in Sweden Sahebekhtiari et al (2011 in Iran, Chaudhary andPayasi, 2013 in India andRall et al (2013) in Brazil.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Antimicrobial sensitivity tests of Staphylococcus aureus as seen in this study agrees with earlier reports by Kalmus et al (2011), who reported a heightened resistance of Staphylococcus aureus to Penicillin and Ampicillin. There is no scientific evidence as to the resistance pattern of mastitis pathogens to penicillin and the Cephalosporin group, but there were widespread reports of antimicrobial drug resistance among Staphylococcus pathogens for over 2-3 decades as earlier reported by Kalmus et al (2011) in Estonia, Botrel et al (2010) in Germany; Persson et al, 2011in Sweden Sahebekhtiari et al (2011 in Iran, Chaudhary andPayasi, 2013 in India andRall et al (2013) in Brazil.…”
Section: Discussionsupporting
confidence: 82%
“…There is no scientific evidence as to the resistance pattern of mastitis pathogens to penicillin and the Cephalosporin group, but there were widespread reports of antimicrobial drug resistance among Staphylococcus pathogens for over 2-3 decades as earlier reported by Kalmus et al (2011) in Estonia, Botrel et al (2010) in Germany; Persson et al, 2011in Sweden Sahebekhtiari et al (2011 in Iran, Chaudhary andPayasi, 2013 in India andRall et al (2013) in Brazil. The trend of resistance patterns to antibiotic use over time showed a long-term effect of over 3-7 years (Rall et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other isolated microorganisms were susceptible to antimicrobials tested. Similar results were reported by Persson et al (2011) when the most of the isolated udder pathogens were susceptible to wide range of antimicrobials, with exception to Penicillin G. Opposite, the other authors reported the high level of resistance of udder pathogens to antimicrobials (Kalmus et al, 2011).…”
Section: P Aeruginosa β-Laktamsupporting
confidence: 75%
“…and Streptococcus spp. was revealed from cases of subclinical mastitis in dairy cows (Roesch et al, 2007;Kalmus et al, 2011). Saini et al (2013) reported higher prevalence of environmental mastitis pathogens and Escherichia coli in dairy herds, predominantly in early lactation.…”
Section: P Aeruginosa β-Laktammentioning
confidence: 99%
See 1 more Smart Citation